2009
DOI: 10.1016/j.ydbio.2008.10.011
|View full text |Cite
|
Sign up to set email alerts
|

Co-operative roles for E-cadherin and N-cadherin during lens vesicle separation and lens epithelial cell survival

Abstract: The classical cadherins are known to have both adhesive and signaling functions. It has also been proposed that localized regulation of cadherin activity may be important in cell assortment during development. In the context of eye development, it has been suggested that cadherins are important for separation of the invaginated lens vesicle from the surface ectoderm. To test this hypothesis, we conditionally deleted N-cadherin or E-cadherin from the presumptive lens ectoderm of the mouse. Conditional deletion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
129
1

Year Published

2009
2009
2014
2014

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 115 publications
(142 citation statements)
references
References 60 publications
10
129
1
Order By: Relevance
“…7R,S) was retained. Furthermore, in AP2α-cre; Ncad Fl/Fl embryos, as expected (Pontoriero et al, 2009), we observed a failure of the lens vesicle to separate from the surface ectoderm and a persistence of P-cadherin expression ( Fig. 7O,P).…”
Section: Research Articlesupporting
confidence: 83%
See 1 more Smart Citation
“…7R,S) was retained. Furthermore, in AP2α-cre; Ncad Fl/Fl embryos, as expected (Pontoriero et al, 2009), we observed a failure of the lens vesicle to separate from the surface ectoderm and a persistence of P-cadherin expression ( Fig. 7O,P).…”
Section: Research Articlesupporting
confidence: 83%
“…Sox1 is first expressed later during invagination of the lens placode, and also during lens morphogenesis in lens fiber cells (Kamachi et al, 1998). Sox2 has been implicated in lens development through its regulation of the δ1-crystallin gene in the chick (Kamachi et al, 2001) and, more recently, of N-cadherin (Matsumata et al, 2005), an adhesion molecule known to be required for normal lens morphogenesis and the differentiation of lens fiber cells (Pontoriero et al, 2009). It has also been proposed that the Sox2 gene is regulated by the Sox2 protein product in combination with Pax6 through the N-3 enhancer that is active in the presumptive lens (Inoue et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…The abnormal development of the entire eyeball, including the retina and iris in Pik3c3 flox/flox ;MLR10-Cre mice, may be a secondary result of impaired lens development, as similar phenotypes were reported in other mouse models with lens-specific deletion of fibroblast growth factor receptor (33), PKC (34), ␤1-integrin (35), ␤-catenin (36), and N/E-cadherin (55). Alternatively, it may be due to an off-target effect of MLR10-Cre expression in non-lens tissues in the eye.…”
Section: Discussionmentioning
confidence: 59%
“…These cells do not elongate and differentiate into primary lens fibers as seen in the wild-type lenses. E-cadherin is an epithelial marker , Pontoriero et al, 2009, Zeisberg and Neilson, 2009 whose expression is suppressed in the differentiating epithelial cells in wild-type lenses. Such persistent ectopic expression of E-cadherin and AP-2a has also been observed in Prox1 knockout mice (Wigle et al, 1999).…”
Section: Discussionmentioning
confidence: 99%